Designing PBL-Based Mobile Learning: A Needs Analysis for Enhancing 21st Century Skills in Vocational Schools - Yolanda Idha Fitri; Yeka Hendriyani; Muhammad Giatman; Resmi Darni (STAI Hubbulwathan Duri, 2025)
Advancements in information and communication technology have significantly transformed educational practices, including those in vocational high schools. Preparing students with 21st-century competencies—such as creativity, critical thinking, collaboration, and communication—has become increasingly essential, particularly in the digital era. This study aimed to assess the need for developing a mobile learning application using a problem-based learning (PBL) approach for the static routing topic within the Network Infrastructure Administration course at vocational high schools (SMK). The research involved both students and teachers as respondents to identify learning gaps, assess student competencies, and determine the desired features for an effective mobile learning tool. Findings revealed that a mobile learning solution incorporating the PBL approach holds significant potential to enhance students’ understanding of static routing concepts. The analysis indicated that learners struggle with abstract technical content and benefit from interactive and contextualized learning strategies. The study highlights that mobile learning applications designed with PBL principles can bridge existing instructional gaps by fostering self-directed learning and critical thinking. Key considerations for development include accessibility, engaging interactive features, and integration of problem-solving tasks aligned with real-world scenarios.